Virtual reality and mental training - Frank, C. (Advances in mental skills training, 2021)
In both research and applied sport settings, Virtual Reality (VR) is a rapidly growing field. VR as a simulation of the real world can be distinguished from augmented realities: On a virtuality continuum, VR is at one end with the real world at the other end, whereas augmented re-ality (AR) lies between the two, a primarily real environment augmented by virtual aspects. Thus, in contrast to AR, VR in the domain of sport is considered "as instances when individuals are engaged in a sport that is represented in a computer-simulated environment which aims to induce a sense of being mentally or physically present and enables interactivity with the environment". Immersion is the essential criterion for VR, allowing humans "to participate in the virtual world rather than use it". Although one goal of VR is to simulate reality, VR can be more than a copy of our real world: "the real power of VR is to go beyond what is real, it is more than simulation, it is also creation, allowing us to step out of the bounds of reality and experience paradigms that are otherwise impossible". In the domain of sports, VR allows not only for recreating sports and training environments but also for creating new experiences. "In the future, cyberspace will acquire greater prominence thanks to new technologies. These technologies are going to drastically influence the application of psychological training programs". Although research on VR is growing, VR has not yet paved its way for being a standard tool in applied sport psychology. Results of VR studies on anxiety/pressure, attentional focus, observation, and imagery indicate that VR may be a valuable way to augment mental training. Future directions of VR for sport psychology and VR-based mental training may include extending VR research to goal-setting, self-talk, and other mental techniques and skills; bringing research from the laboratory to the field; and developing recommendations and guidelines for practitioners. Research questions relating to VR-based mental training are highly interdisciplinary as they relate to the technical requirements of VR systems and to their applicability according to the needs of athletes, teams and their coaches. Accordingly, addressing these questions will require the collaborative effort of research teams, applied practitioners, and hitech developers. Collaborative research is warranted to explore the potentials and limits of immersive, interactive VR systems together with related embodied experiences for future VR-based mental training.